Genetic Architecture and Association Studies for Grain Yield and its attributing Traits in Recombinant Inbred Lines for Sodicity Tolerance in Rice (Oryza sativa L.) - Upadhyay, Sameer; Rathi, Sanket; Choudhary, Madhu; Singh, Pawan Kumar; Loitongbam, Bapsila; Bisen, Prashant; Verma, Om Prakash; Behara, Sasmita; Singh, Namita; Singh, Ramesh Kumar (International Journal of Bio-resource and Stress Management, 2022)
The present study was undertaken at NSP Unit 6 Agricultural Research Farm and Main Experimental Station of Acharya Narendra Dev University of Agriculture and Technology, Uttar Pradesh, India, from July to November 2020, in which genetic variability and heritability of 250 recombinant inbred lines (F7) and their parents PUSA 44 and CSR 43 were evaluated and correlation studies were performed for grain yield and yield contributing traits. The experiment was conducted in two replications at two different and naturally occurring sodic conditions following α-lattice design. Analysis of variance revealed significant variations among the lines depicting inherent variability between lines. For attributes, viz., plant height, effective tillers plant-1, spikelet fertility percentage, test weight and grain yield plant-1, high phenotypic and genotypic coefficient of variation estimates were observed for both the locations indicating good scope for selection based on these traits. However, the attributes viz., test weight and effective tillers plant-1 values depicted the pertinent role of the environment and thus, require careful assessment in selection programs concerning these traits. For days to 50% flowering, filled grains panicle-1, spikelet fertility percentage, and grain yield plant-1, moderate heritability was discovered with a high genetic advance as a percentage of mean, indicating that there is less influence of environment over these traits. Correlation studies revealed a significant and positive association with these yield attributing traits. Mutual association between component traits exhibit variable responses at both locations, validating genotype and environment interactions among traits with respect to yield.